2020
DOI: 10.1177/1010428320951057
|View full text |Cite
|
Sign up to set email alerts
|

Expression of voltage-dependent anion channels in endometrial cancer and its potential prognostic significance

Abstract: The exchange of metabolites between mitochondria and cytosol occurs through pores formed by voltage-dependent anion channel proteins. Voltage-dependent anion channels appear to be master regulators of mitochondrial bioenergetics and the intracellular flow of energy. Deregulation of voltage-dependent anion channels expression is thought to be related to mitochondrial dysfunction in cancer. The aim of this study was to investigate the mRNA and protein expression levels of VDAC1, VDAC2, and VDAC3 in relation to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…The expression of voltage-dependent anion channels (VDACs) on the mitochondrial membrane of all eukaryotes, including mammals [ 96 ], is increased in various tumor tissues, such as carcinoma of the breast [ 97 ], colon [ 98 ], thyroid gland [ 99 ], lung [ 100 ], pancreas [ 101 ], and liver [ 102 ] compared with that in normal tissues. The VDAC1, 2, and 3 isotypes of these channels play different roles; VDAC1 and VDAC2 participate in pore formation within the mitochondrial membrane [ 96 ] and VDAC3 participates in the regulation of mitochondrial membrane potential [ 103 ]. The expression of VDAC is associated with neurodegenerative disorders and muscular and myocardial diseases including various types of cancers [ 104 ].…”
Section: Membrane-associated Components Of Chloride Movementmentioning
confidence: 99%
“…The expression of voltage-dependent anion channels (VDACs) on the mitochondrial membrane of all eukaryotes, including mammals [ 96 ], is increased in various tumor tissues, such as carcinoma of the breast [ 97 ], colon [ 98 ], thyroid gland [ 99 ], lung [ 100 ], pancreas [ 101 ], and liver [ 102 ] compared with that in normal tissues. The VDAC1, 2, and 3 isotypes of these channels play different roles; VDAC1 and VDAC2 participate in pore formation within the mitochondrial membrane [ 96 ] and VDAC3 participates in the regulation of mitochondrial membrane potential [ 103 ]. The expression of VDAC is associated with neurodegenerative disorders and muscular and myocardial diseases including various types of cancers [ 104 ].…”
Section: Membrane-associated Components Of Chloride Movementmentioning
confidence: 99%
“…In particular, a role of isoform 3 in the hepatocarcinogenesis induced by HBV infection was proposed by Zhang et al (2018 , 2020) : a specific miRNA (miR-3928v) was shown to directly target and down-regulate VDAC3 expression and to promote hepatocarcinoma malignancy, by a still unclarified molecular mechanism. Recently, Józwiak et al (2020) reported a significant increase in VDAC3 expression in non-metastatic endometrial cancers compared to normal tissue 1 . However, alterations in VDAC isoform 3 mRNA levels have also been registered in pathologies different from cancer, such as chronic unpredictable stress ( Chakravarty et al, 2013 ), cerebral malaria ( Desruisseaux et al, 2010 ), and viral infections ( Avantaggiati et al, 1993 ; Rahmani et al, 2000 ; Waris et al, 2001 ).…”
Section: Role Of Voltage-dependent Anion Selective Channel 3 In Pathologiesmentioning
confidence: 99%
“…Beyond the role in mitochondrial metabolism, VDAC is also a prognostic biomarker for certain types of human cancer ( Jozwiak et al, 2020 ; Wersall et al, 2021 ). High expression of VDAC1 has been associated with unfavorable outcomes in cancers from lung, head and neck, breast, and liver ( Grills et al, 2011 ; Yang et al, 2019 ; Jozwiak et al, 2020 ).…”
Section: Vdac Opening Mitochondrial Metabolism and Warburg Effectmentioning
confidence: 99%
“…Beyond the role in mitochondrial metabolism, VDAC is also a prognostic biomarker for certain types of human cancer ( Jozwiak et al, 2020 ; Wersall et al, 2021 ). High expression of VDAC1 has been associated with unfavorable outcomes in cancers from lung, head and neck, breast, and liver ( Grills et al, 2011 ; Yang et al, 2019 ; Jozwiak et al, 2020 ). High transcript levels of VDAC2 in multiple tumors, including melanoma, epithelial thyroid tumors, and breast cancer have been reported in the cancer databases cBioportal, 1 and the Human Protein Atlas.…”
Section: Vdac Opening Mitochondrial Metabolism and Warburg Effectmentioning
confidence: 99%